(untitled) (Journal of Comparative Research in Anthropology and Sociology, 2025)
This article examines the traditional status of the family in the contemporary Arab Gulf, highlighting how Arab families maintain their cultural identity amid rapid modernization. The focus is on the enduring importance of family unity and family life as key dimensions of both social cohesion and individual quality of life. The analysis draws on research findings concerning the Arab family in the six Gulf Cooperation Council (GCC) member states: Kuwait, Bahrain, Oman, Qatar, the Emirate of Dubai (UAE), and Saudi Arabia. Established in 1981, the GCC represents a regional alliance shaped by shared cultural and economic interests. This study explores how traditional family structures persist and adapt in a region undergoing major socio-economic changes. It considers the transformation of the Arab family from traditional to modern forms, reflecting on broader themes such as multiculturalism, feminism, and modernity. These shifts occur in the context of rapid development driven by the capitalization of oil and gas resources since the 1970s. This article emphasizes the deeper cultural and social foundations that continue to define Arab identity. The resilience of family structures offers insight into how modernization can coexist with tradition.